THE EFFECT OF INCLUSIVE LEADERSHIP ON EMPLOYEE ENGAGEMENT AT THE ARGA MAKMUR CLASS IIB CORRECTIONAL INSTITUTION - Achmad Aldi Al Faruq; Padmono Wibowo (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the effect of inclusive leadership on employee engagement at Class IIB Arga Makmur Correctional Institution. Inclusive leadership is viewed as a leadership approach that creates a supportive, participatory work environment and appreciates diversity, thereby encouraging stronger employee involvement in their work. The research uses a quantitative approach, with data collected through questionnaires distributed to employees. The collected data were analyzed using simple linear regression with the assistance of IBM SPSS. The findings indicate that inclusive leadership has a positive and significant influence on employee engagement. Leaders who adopt an inclusive leadership style are able to build a more open and supportive work atmosphere, which encourages employees to feel valued, actively participate, and show greater commitment to their work. Therefore, the implementation of inclusive leadership practices can be an effective strategy for increasing employee engagement within the organization. Keywords: Inclusive Leadership; Work Engagement; Correctional Institutions